Perbandingan Kadar Natrium Serum pada Pasien Gagal Ginjal dan Non-Gagal Ginjal Menggunakan Elektrolit Analyzer Cornley - Nurul Siamtryningsih; Yayuk Mundriyastutik; Arief Adi Saputro (Jaringan Laboratorium Medis, 2026)
Kidney failure is the inability of the kidneys to filter blood and maintain electrolyte balance, particularly sodium, which plays an important role in regulating body fluids and neuromuscular activity. Sodium imbalance, such as hyponatremia, often occurs in patients with kidney failure due to impaired excretion, thereby increasing the risk of neurological and cardiovascular complications. This study aimed to compare serum sodium levels between patients with kidney failure and those without kidney failure using the Cornley Electrolyte Analyzer.This research employed a quantitative approach with a cross-sectional design, involving a random sample of 88 respondents (44 patients with kidney failure and 44 without kidney failure) at Al-Ikhlas Islamic Hospital, Pemalang, without considering gender, aged 18–70 years. Serum sodium levels were measured using the ion-selective electrode (ISE) technique. Data analysis included univariate analysis (descriptive statistics and Shapiro-Wilk normality test) and bivariate analysis (Mann-Whitney U test) at a significance level of α=0.05. The results showed that the median serum sodium level in kidney failure patients was 134.5 mmol/L (IQR=9), indicating a higher tendency toward hyponatremia, while non-kidney failure patients had a mean of 137.58 mmol/L (SD=6.70), reflecting greater stability. Statistical analysis demonstrated a significant difference (p=0.014), with higher sodium levels observed in the non-kidney failure group. In conclusion, there is a significant difference in serum sodium levels between the two groups, where patients with kidney failure are more prone to hyponatremia. Therefore, routine electrolyte monitoring and adherence to a low-sodium diet are necessary.